The Lifestyle Modifications and Endometrial Proteome Changes of Women With Polycystic Ovary Syndrome and Obesity - Abdulkhalikova, D.; Sustarsic, A.; Vrtačnik Bokal, Eda; Jancar, N.; Jensterle, M.; Burnik Papler, T. (Frontiers in Endocrinology, 2022)
Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age. Affected women have elevated prevalence for overweight and obesity. In our study we sought to determine how weight loss associated with lifestyle changes affect endometrium specific proteome, endocrine-metabolic characteristics and motor capabilities of obese women with PCOS and infertility. 12 infertile women under the age of 38 with PCOS and BMI ≥30 kg/m2 were included in the study. An evaluation was performed by a gynecologist and an endocrinologist. The weight-loss program lasted 8 weeks under the guidance of a professional trainer. Endometrial sampling during a period of implantation window for proteome determination was performed before and after weight loss. In endometrial samples at the end of the study increased protein abundance was recorded for Legumain, Insulin-like growth factor-binding protein 7, Hepatocyte growth factor receptor, Keratin, type II cytoskeletal 7 and Cystatin-B, while the B-lymphocyte antigen CD20 protein abundance was decreased. Our results also indicate significantly lowered fasting blood glucose level and free testosterone concentration and significant improvements in body composition and physical capacity. This study may open up the venues for investigating important biomarkers, that may affect endometrial receptivity.